A reliable risk score for stage IV esophagogastric cancer - Blank, Susanne; Lordick, F.; Dobritz, M.; Grenacher, Lars; Burian, Maria; Langer, R.; Roth, Wilfried; Schaible, Anja; Becker, K.; Bläker, Hendrik; Peters, Leila; Stange, Annika; et al. (European journal of surgical oncology, 2013)
Background - The role of surgery for patients with metastatic esophagogastric adenocarcinoma (EGC) is not defined. The purpose of this study was to define selection criteria for patients who may benefit from resection following systemic chemotherapy. - Methods - From 1987 to 2007, 160 patients presenting with synchronous metastatic EGC (cT3/4 cNany cM0/1 finally pM1) were treated with chemotherapy followed by resection of the primary tumor and metastases. Clinical and histopathological data, site and number of metastases were analyzed. A prognostic score was established and validated in a second cohort from another academic center (n = 32). - Results - The median survival (MS) in cohort 1 was 13.6 months. Significant prognostic factors were grading (p = 0.046), ypT- (p = 0.001), ypN- (p = 0.011) and R-category (p = 0.015), lymphangiosis (p = 0.021), clinical (p = 0.004) and histopathological response (p = 0.006), but not localization or number of metastases. The addition of grading (G1/2:0 points; G3/4:1 points), clinical response (responder: 0; nonresponder: 1) and R-category (complete:0; R1:1; R2:2) defines two groups of patients with significantly different survival (p = 0.001) [low risk group (Score 0/1), n = 22: MS 35.3 months, 3-year-survival 47.6%); high risk group (Score 2/3/4) n = 126: MS 12.0 months, 3-year-survival 14.2%]. The score showed a strong trend in the validation cohort (p = 0.063) [low risk group (MS not reached, 3-year-survival 57.1%); high risk group (MS 19.9 months, 3-year-survival 6.7%)]. - Conclusion - We observed long-term survival after resection of metastatic EGC. A simple clinical score may help to identify a subgroup of patients with a high chance of benefit from resection. However, the accurate estimation of achieving a complete resection, which is an integral element of the score, remains challenging.